Working with Ferns Issues and Applications - Fernández, Helena; Kumar, Ashwani; Revilla, Maria Angeles; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Ferns existing today represent a genetic inheritance of great value as they include species of ancient vascular plants, which have direct connection with the crucial steps done in the past for settling life on Earth. Their life cycle is an example of alternation of generations, in which both a multicellular diploid organism and a multicellular haploid organism occur and give rise to the other. Spore, gametophyte and sporophyte have been studied either for basic and practical purposes. In the first case, they offer us simple and easy to grow experimental systems to investigate on plant development, and secondly, they are culture by their ornamental appeal, their environmental benefit or as source of metabolites. This timely volume brings a selection of chapters, each one composed by experts in their respective fields. The chapters included cover a broad range from the knowledge of its biology and contribution to understanding of plant development, useful protocols for propagation and conservation purposes, genetic variability as well as environmental and theurapeutical applications. This wide spectrum of the contributions gives to reader a rapid idea of the enormous potential of this plant group. The originality of this book is to expose the most recent tendencies in their investigation, which is far from the traditional perspective usually followed. The collected articles in this volume incorporate most of novel techniques used nowadays routinely to resolve traditional questions. Ashwani Kumar Professor, Department of Botany, University of Rajasthan, Jaipur. The author’s repertoire of published works spreads across 150 research articles in various national and international journals. He has an experience of over three decades in his field of research, namely, tissue culture and biochemistry, being awarded with prestigeous V. Puri Medal in 2008 for his services to advancement of Botany. Helena Fernández Associate Professor, Department of Biology of Organisms and Systems, Oviedo University, Spain. Her research focuses on micropropagation and reproduction in ferns during the two last decades. In 2002 she obtained the award “Ramón y Cajal” by The Ministry of Science and Technology, being engaged to the Oviedo University as tenurer, full time, in the Area of Plant Physiology since then. M. Angeles Revilla Plant Physioloy Assistant Professor in the Biology Faculty at the Oviedo University (Spain) since 1987. Twenty years experience in plant tissue culture. She has also worked in cryopreservation and genetic stability for the last ten years, mainly in the development of protocols for in vitro shoot apices in agronomic species.
CONTRIBUTION OF FERNS TO UNDERSTANDING OF PLANT DEVELOPMENT -- Cellular, Molecular, and Genetic Changes During the Development of Ceratopteris richardii Gametophytes -- Laboratory-Induced Apogamy and Apospory in Ceratopteris richardii -- Sexual Reproduction in Ferns -- Gibberellic Acid and Ethylene Control Male Sex Determination and Development of Anemia phyllitidis Gametophytes -- The Sporophytes of Seed-Free Vascular Plants – Major Vegetative Developmental Features and Molecular Genetic Pathways -- PROPAGATION, CONSERVATION AND CONTROL OF GENETIC VARIABILITY IN FERNS -- From Spore to Sporophyte: How to Proceed In Vitro -- In Vitro Regeneration Systems of Platycerium -- Stipule Propagation in Five Marattioid Species Native to Taiwan (Marattiaceae; Pteridophyte) -- Tree Ferns Biotechnology: From Spores to Sporophytes -- In Vitro Propagation of Rare and Endangered Serpentine Fern Species -- Conservation of Fern Spores -- Exploration of Cryo-methods to Preserve Tree and Herbaceous Fern Gametophytes -- Pteridophyte spores viability -- Microsatellites: A Powerful Genetic Marker for Fern Research -- Diversity in Natural Fern Populations: Dominant Markers as Genetic Tools -- ENVIRONMENTAL BIOTECHNOLOGY: ECOTOXICOLOGY AND BIOREMEDIATION IN FERNS -- Mitochondrial Activity of Fern Spores for the Evaluation of Acute Toxicity in Higher Plant Development -- Chronic Phytotoxicity in Gametophytes: DNA as Biomarker of Growth and Chlorophyll Autofluorescence as Biomarker of Cell Function -- Arsenic Hyperaccumulator Fern Pteris vittata: Utilities for Arsenic Phytoremediation and Plant Biotechnology -- Aerobiology of Pteridophyta Spores: Preliminary Results and Applications -- THERAPEUTICAL/MEDICINAL APPLICATIONS -- Studies on Folk Medicinal Fern: An Example of “Gu-Sui-Bu” -- Ecdysteroids in Ferns: Distribution, Diversity, Biosynthesis, and Functions -- Ferns: From Traditional Uses to Pharmaceutical Development, Chemical Identification of Active Principles -- Functional Activities of Ferns for Human Health -- Toxicological and Medicinal Aspects of the Most Frequent Fern Species, Pteridium aquilinum (L.) Kuhn.
Keywords: Plant science; Botany; Plant Sciences